Epidemiology of fetal cerebral ventriculomegaly and evaluation of chromosomal microarray analysis versus karyotyping for prenatal diagnosis in a Chinese hospital. Issue 11 (November 2019) - Yi, Jun-Ling; Zhang, Wei; Meng, Da-Hua; Ren, Li-Jie; Yu, Jin; Wei, Yi-Liang
Objective: To evaluate the efficiency and incremental value of chromosomal microarray analysis as compared with standard karyotyping for the identification of genomic abnormalities in fetal DNA. Methods: This retrospective study enrolled female patients with ultrasonographically diagnosed fetal ventriculomegaly. The prevalence, associated anomalies and clinical outcomes of ventriculomegaly were evaluated based on data from a single maternal and child health hospital in southwest China. Results: A total of 943 cases of ventriculomegaly were analysed in this study, which were diagnosed at a mean ± SD gestational age of 23.8 ± 8.2 weeks. Non-isolated ventriculomegaly cases had a significantly higher maternal age than isolated cases (29.6 ± 5.5 versus 27.9 ± 4.2 years, respectively) and were also associated with a larger proportion of bilateral (56.1% versus 46.7%, respectively) and severe (12.8% versus 3.7%, respectively) ventriculomegaly. There were 97 cases detected by both karyotyping and microarray analysis. All apparent chromosome abnormalities identified upon karyotyping were detected with the use of microarray analysis. Microarray analysis also reported genetic abnormalities in 20 additional cases not detected by karyotyping. Of these additional 20 cases, 9.3% of pregnancies reported standard genetic variants for clinically relevant information, whereas 11.3% reported uncertain genetic abnormalities. Conclusion: Chromosomal microarray analysis is an efficient tool, significantly increasing the diagnostic power for prenatal diagnosis.